Captain Underpants. 1, The first epic manga - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Adventures of Captain Underpants (Manga), 2026)
Combining humor and action with empowerment and empathy, Captain Underpants: The First Epic Manga features the amazing adventures of best friends George Beard and Harold Hutchins and their waistband warrior superhero creation, Captain Underpants! He's faster than a speeding waistband, more powerful than boxer shorts, and able to leap tall buildings without getting a wedgie. Night and day, Captain Underpants fights for truth, justice, and all that is pre-shrunk and cottony!